Synthesis, potential antitumor activity, cell cycle analysis, and multitarget mechanisms of novel hydrazones incorporating a 4-methylsulfonylbenzene scaffold: a molecular docking study - Alaa A.-M; Adel S. El-Azab; Nawaf A. AlSaif; Ahmad J. Obaidullah; Abdulrahman M. Al-Obaid; Ibrahim A. Al-Suwaidan (Taylor & Francis Group, 2021)
Hydrazone is a bioactive pharmacophore that can be used to design antitumor agents. We synthesised a series of hydrazones (compounds 4-24) incorporating a 4-methylsulfonylbenzene scaffold and analysed their potential antitumor activity. Compounds 6, 9, 16, and 20 had the most antitumor activity with a positive cytotoxic effect (PCE) of 52/59, 27/59, 59/59, and 59/59, respectively, while compounds 5, 10, 14, 15, 18, and 19 had a moderate antitumor activity with a PCE of 11/59-14/59. Compound 20 was the most active and had a mean 50% cell growth inhibition (GI50) of 0.26 µM. Compounds 9 and 20 showed the highest inhibitory activity against COX-2, with a half-maximal inhibitory concentration (IC50) of 2.97 and 6.94 μM, respectively. Compounds 16 and 20 significantly inhibited EGFR (IC50 = 0.2 and 0.19 μM, respectively) and HER2 (IC50 = 0.13 and 0.07 μM, respectively). Molecular docking studies of derivatives 9, 16, and 20 into the binding sites of COX-2, EGFR, and HER2 were carried out to explore the interaction mode and the structural requirements for antitumor activity.